Analisis Representasi Kerja Sama Generasi Tua dan Generasi Muda Serta Etos Kerja dalam Film The Intern - Nadhira Afifah; Annory Langga’o (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2026)
This research aims to understand the representation of cooperation between the older and younger generations and work ethic in the film "The Intern" by Nancy Meyers. This research uses a descriptive qualitative approach with Charles Sanders Peirce's semiotic analysis in the form of a meaning triangle, namely sign, object, and interpretant. Signs are in the form of visuals, dialogue, and symbols. The object is what the sign represents, and the interpretant is the understanding derived from both the sign and the object. In this study, the researcher carried out an analysis by selecting each scene that shows generational differences, the emergence of cooperation, and the work ethic applied in the film The Intern. We collected data through library research, which included relevant books, articles, and scientific writings. The data collection techniques used are interviews, observations, and documentation. The results of this research show that this film succeeded in presenting generational differences not as obstacles but as a way to work together well and develop. This film demonstrates work ethic values such as hard work, responsibility, honesty, and cooperation. This research concludes that the film The Intern is not only entertaining but also provides many social messages about cooperation and work ethic.